Smart Safety and Accident Prevention System for Mountain Roads - Saha, Dwaipayan; Mukherjee, Indrani; Roy, Jesmin; Chatterjee, Sumanta (International Journal of Computer Sciences and Engineering, 2020)
Accidents are more common now a days and prevention of accidents is really a great concern of people. So an accident prevention system is of great help and so our paper deals with a smart road safety and prevention system to avoid road accidents .Here sensors are used along with Arduino and for indication purposes IR sensors, buzzers and RGB LED light are used. Here we are using a counter to keep the count of vehicles passing through the road. To overcome the accidents due to curve and narrow roads this safety system is preventive. The main purpose of this paper is to make a safety road system to reduce the number of road accidents due to curvy and narrow roads. This indication system gives indication to the vehicles that other vehicles are coming from the other side so that they can take the safety measures before hand only.